Enhancing Cementitious Materials: A Detailed Review of Bentonite’s Role in Optimizing Concrete Performance - Zakaria Mekhnache; Tewfik Ali-Dahmane; Zine-El-Abidine Kameche; Ivan Alhama-Manteca; Ahmed Sofiane Benosman; Sidi-Mohammed Aissa-Mamoune (Journal of Building Materials and Structures)
Cement manufacturing significantly impacts global CO₂ emissions, contributing around 8% due to its high energy demand and the calcination process in clinker production. To reduce this environmental impact, the industry is exploring sustainable alternatives by integrating supplementary cementitious materials (SCMs), which enhance cement properties and lower its carbon footprint, aligning with sustainable construction goals. One such material is bentonite, a naturally occurring clay with high plasticity and excellent water retention properties. When added to cement mixtures, bentonite improves essential properties like decreasing permeability, enhancing workability, and boosting chemical resistance. Its pozzolanic activity aids in long-term strength development, making it valuable for standard and specialized applications, including geotechnical engineering and waste containment. Bentonite supports environmental sustainability by reducing cement demand thus lowering CO₂ emissions and by increasing durability, which extends the lifespan of structures and cuts down on maintenance costs. This discussion will explore the various environmental and mechanical benefits of bentonite as a sustainable additive in cementitious systems and highlight studies that have demonstrated its effectiveness in promoting more eco-friendly construction practices.